Asymmetric Graves’ Orbitopathy - Panagiotou, Grigorios; Perros, Petros (Frontiers in Endocrinology, 2020)
Graves’ Orbitopathy (GO) is an autoimmune orbital disorder usually presenting as a sequala of autoimmune thyroid disease. The presence of GO is associated with increased psychological burden and, in severe cases may cause blindness. While most patients with GO present with bilateral disease, asymmetric or unilateral GO may affect a significant proportion of patients diagnosed with GO. Older age, male sex, active and severe disease correlate with asymmetric disease. However, the exact mechanisms causing asymmetry remain elusive. Herein, we review the literature on asymmetric GO and highlight its differences compared with bilateral GO.